Determination of the Cytostatic and Cytocidal Activities of Antimalarial Compounds and Their Combination Interactions. Issue 4 (1st December 2014) - Sherlach, Katy S.; Roepe, Paul D.
Abstract: Determining the antiplasmodial activity of candidate antimalarial drugs in vitro identifies new therapies for drug‐resistant malaria. Importantly though, activity can be either growth‐inhibitory (cytostatic) or parasite‐kill (cytocidal), or both. The simple methods described here can allow for distinction between these activities, as well as definition of drug interactions between two or more compounds. The latter is important in the definition of novel drug combination therapy for malaria. These methods involve live malarial parasite red blood cell culture, routine pharmacology, high‐throughput detection of parasite DNA with fluorescent reporters, and routine mathematical analysis of dose‐response curves. The techniques and approaches are accessible to most laboratories and require minimal special equipment beyond a fluorescent plate reader and tissue culture facilities. © 2014 by John Wiley & Sons, Inc.